The effect of thermal injury on gastric emptying in rats - YEGEN, BERRAK; YEGEN, ŞEVKET CUMHUR (My University, 1995)
Gastric distension and gastrointestinal discomfort are common complications of burn injuries. This study was designed to examine the effect of thermal injury on the emptying rate of liquids in conscious rats fitted with stainless steel cannulae in the body of the stomach. In rats with partial-thickness burns emptying of the hyperosmolal saline was found to be delayed (P < 0.05) with respect to control only during the chronic phase of injury. However, full-thickness burns delayed hyperosmolal saline emptying in both acute and chronic phases, together with delayed saline emptying in the acute state. Thermal injury did not influence the gastric emptying of peptone and acid solutions, which activate different pathways to delay gastric emptying. Delayed gastric emptying of hyperosmolal solutions may be explained by increased sympathetic and opiatergic nervous activities, resulting in reflex relaxation of gastric smooth muscle. © 1995.